(untitled) (Homiletic, 2023)
Fred Craddock in his textbook Preaching advised homiletics students to read a short story a week to help them become engaging preachers. He said that by taking the initiative to do so, students would relieve their professor of the contradiction of having to assign such reading. However, since most students will not read short stories on their own, teachers of preaching need to advocate and make room for them in their homiletics courses. Short stories offer instruction in unity, brevity, open-endedness, vocabulary, and difficulty. Also, short story collections can inspire one to preach a sermon series. This article discusses these short story traits and how teachers of preaching can introduce short stories to their students.